Accuracy of a Mobile App to Identify Suspect Asbestos-Containing Material in Australian Residential Settings - Govorko, M.; Fritschi, Lin; Reid, A. (2018)
In situ asbestos in the built environment is a remaining source of exposure in countries that have prohibited the manufacture and use of asbestos. However, it is difficult to identify in situ asbestos-containing material in residential settings. The objective of this study was to evaluate the accuracy of the mobile phone application ("app"), ACM Check, in identifying in situ asbestos located inside and outside of homes compared with onsite inspections conducted by an experienced environmental consultant. A cross-sectional study was undertaken that involved participants completing ACM Check on their homes built pre-1990 and located throughout metropolitan Perth, Western Australia, and an onsite inspection conducted at each home by an environmental consultant. Cohen's kappa statistic was calculated to evaluate the strength of agreement between the two methods. The 40 houses sampled were built between 1898 and 1988 with a median year of 1966. Thirty eight (95%) homes had at least one type of material categorized as positive for asbestos by both ACM Check and the environmental consultant (? = 1.00). Agreement between the two methods differed when categorizing specific materials as positive or negative for asbestos with substantial agreement for fencing (? = 0.918), outbuilding walls (? = 0.844), backing board to electrical meter box (? = 0.826), exterior wall cladding (? = 0.771), and interior walls (? = 0.754), and fair agreement for outbuilding roofs (? = 0.375), and interior flooring (? = 0.304). ACM Check is a tool that can be used by tradespeople, home renovators, and householders to screen residential settings for the presence of in situ asbestos-containing material. Mobile phone apps have the potential to be developed or modified for use in other countries to help users identify asbestos and reduce their risk of asbestos exposure.